The Effect of Concentration of Lawsonia inermis as a Corrosion Inhibitor for Aluminum Alloy in Seawater - F. Zulkifli; Nora'aini Ali; M. Sukeri M. Yusof; WanM. Khairul; Rafizah Rahamathullah; M. I. N. Isa; W. B.Wan Nik (Hindawi, 2024)
Indexed by SCOPUS